Reseñas de libros (Revista Peruana de Investigación Educativa, 2009)
Mertens, D. (2005). Research and Evaluation in Education and Psychology.Integrating Diversity with Quantitative, Qualitative, and Mixed Methods.2da. ed. Thousand Oaks, CA: SAGE.